2020
DOI: 10.1177/0022042620921351
|View full text |Cite
|
Sign up to set email alerts
|

Peers, Perceptions, and E-Cigarettes: A Social Learning Approach to Explaining E-Cigarette Use Among Youth

Abstract: This study uses social learning theory to examine whether differential associations with e-cigarette-using peers is related to personal e-cigarette use among youth, and the extent to which this relationship is explained by personal risk perceptions of e-cigarettes. Moreover, this study tests whether the mediation process is moderated by type of e-cigarette user. This study uses a sample of high school seniors from the 2016 Monitoring the Future Study ( N = 2,100), and a subsample of e-cigarette users ( n = 523… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 83 publications
(93 reference statements)
2
11
0
Order By: Relevance
“…As our findings provide further support for the many studies that have found that peer smoking influences teenage e-cigarette use [ 20 , 47 50 ], we suggest that health education interventions that take account of peer influences remain important, particularly as higher levels of peer e-cigarette use [ 51 , 52 ] and favourable e-cigarette peer norms [ 53 ] have been found by other researchers to be related to higher odds of personal e-cigarette use.…”
Section: Discussionsupporting
confidence: 86%
“…As our findings provide further support for the many studies that have found that peer smoking influences teenage e-cigarette use [ 20 , 47 50 ], we suggest that health education interventions that take account of peer influences remain important, particularly as higher levels of peer e-cigarette use [ 51 , 52 ] and favourable e-cigarette peer norms [ 53 ] have been found by other researchers to be related to higher odds of personal e-cigarette use.…”
Section: Discussionsupporting
confidence: 86%
“…2,3 While there remains a degree of controversy within public health about the extent to which e-cigarettes should be made available to the public to assist smoking cessation efforts, 4 there is general agreement that under-age use of the devices is to be avoided because of the associated adverse health consequences and the potential for children and youth to become addicted to nicotine. 5,6 Schools are recognised as important venues for vaping prevention interventions because of: (i) the critical role of peer influence in affecting e-cigarette uptake, 7 (ii) the extent to which children and youth have been found to be exposed to students vaping on school premises, 8,9 (iii) the demonstrated association between noticing peers vaping at school and becoming a user 10,11 and (iv) school use being an indicator of greater overall vaping frequency among students. 12 Schools also constitute settings in which children are exposed to education about the harms associated with e-cigarette use and policies that aim to minimise exposure and reinforce messages about the importance of avoiding these products.…”
mentioning
confidence: 99%
“…Namely, a variety of factors associated with prominent criminological theories are related to e-cigarette use-although researchers, being from a variety of disciplines, have not always described these correlates in terms of indicators of criminological theories. For example, consistent with social learning theory (Akers, 1977;Burgess & Akers, 1966), several studies have found that peer attitudes, risk perceptions, and peer use of e-cigarettes are predictors of personal e-cigarette use (Barrington-Trimis et al, 2015;Hanewinkel & Isensee, 2015;Perikleous et al, 2018;Rocheleau et al, 2020;Vogel et al, 2018;Wallace & Roche, 2018). In addition, prior research on correlates of e-cigarette use has also been consistent with the general theory of crime (Gottfredson & Hirschi, 1990;Hirschi, 2004), findings show that individuals who are more impulsive, engage in risky behaviors, have weaker executive function ability, receive poorer grades in school, have lower levels of perseverance, who are more rebellious, and have more social cognitive issues are all more likely to use e-cigarettes (Grant et al, 2019;Hanewinkel & Isensee, 2015;Lanza & Teeter, 2018;Pentz et al, 2015;Saddleson et al, 2015;Spindle et al, 2017;Wills et al, 2015Wills et al, , 2017.…”
Section: The Issue Of Confounding Factorsmentioning
confidence: 76%
“…Namely, the same set of factors that cause vaping is likely to cause violent or property crime. Indeed, prior literature has found that many of the same correlates of violence and property crime are related to vaping such as peer attitudes/behaviors (Barrington-Trimis et al, 2015;Hanewinkel & Isensee, 2015;Perikleous et al, 2018;Rocheleau et al, 2020;Vogel et al, 2018;Wallace & Roche, 2018) and self-control (Grant et al, 2019;Hanewinkel & Isensee, 2015;Lanza & Teeter, 2018;Pentz et al, 2015;Saddleson et al, 2015;Spindle et al, 2017;Wills et al, 2015Wills et al, , 2017. Thus, studies that are not able to extensively account for a host of potential confounding factors run the risk of giving the appearance of a relationship when none may, in fact, exist.…”
Section: Discussionmentioning
confidence: 99%